2014
DOI: 10.1016/j.ijrobp.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Randomized Trial in Locally Advanced Rectal Cancer: No Benefit From Adding a Brachytherapy Boost

Abstract: Purpose/Objective(s) Mature data on tumor control and survival are presented from a randomized trial of the addition of a brachytherapy boost to long-course neoadjuvant chemoradiation (CRT) for locally advanced rectal cancer. Methods and Materials Between March 2005 and November 2008, 248 patients withT3-4N0-2M0 rectal cancer were prospectively randomized to either long-course preoperative CRT (50.4Gy in 28 fractions, peroral UFT and L-leucovorin) alone or the same CRT schedule plus a brachytherapy boost (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 34 publications
(44 reference statements)
1
25
1
Order By: Relevance
“…The primary endpoint, pCR rates did not differ (18% in both) but more tumor regressions were seen [26]. In spite of this, again no differences in other outcomes were seen [27]. These results do not exclude that a dose-response relationship is seen also for other and more relevant outcomes than immediate tumor regression.…”
Section: Modifying the Radiationmentioning
confidence: 82%
“…The primary endpoint, pCR rates did not differ (18% in both) but more tumor regressions were seen [26]. In spite of this, again no differences in other outcomes were seen [27]. These results do not exclude that a dose-response relationship is seen also for other and more relevant outcomes than immediate tumor regression.…”
Section: Modifying the Radiationmentioning
confidence: 82%
“…These findings are in contrast to the much larger Danish study which randomized clinically staged T3/T4 rectal cancer patients to either neoadjuvant long‐course CRT alone or the same schedule but with a brachytherapy boost (10 Gy × 2), followed by surgery in both groups. Although there was evidence of tumour regression with brachytherapy boost, the study failed to demonstrate a difference in the ypT0N0 rate or an improvement in local recurrence or survival . The same group have recently reported that in patients with a ‘bad’ low rectal cancer, treatment with high‐dose neoadjuvant CRT and a 5 Gy brachytherapy boost allowed a successful watch‐and‐wait strategy in 78% of patients but with a cumulative local recurrence of 26% at 2 years .…”
Section: Organ Preservationmentioning
confidence: 97%
“…Brachytherapy has also been used as a boost to long-course neoadjuvant chemoradiation in order to achieve dose-escalation in several studies (75-78). Gerard et al was the first to determine if contact therapy as a boost to EBRT could increase the pCR and the sphincter-preservation rate.…”
Section: Contact Therapy and High-dose Rate Brachytherapy (Hdrb)mentioning
confidence: 99%
“…After a median follow of 5.4 years, there was no difference in OS, PFS and freedom from local failure between the 2 groups. The authors concluded that despite an improvement in pCR, the addition of endorectal brachytherapy did not translate into an improvement in OS, PFS and locoregional control (75). …”
Section: Contact Therapy and High-dose Rate Brachytherapy (Hdrb)mentioning
confidence: 99%